2017
DOI: 10.1186/s12872-017-0533-2
|View full text |Cite
|
Sign up to set email alerts
|

Very early recurrence predicts long-term outcome in patients after atrial fibrillation catheter ablation: a prospective study

Abstract: BackgroundLong-term recurrence (LR) is a tendency that re-occurs within 3 months after catheter ablation for atrial fibrillation (AF). Whether very early recurrence (VER) within 7 days of post ablation is a prognostic factor of LR or not is unclear. For this reason, present study sought to examine the relationship between VER and LR.MethodsIn this prospective analysis 378 consecutive patients underwent an initial catheter ablation for paroxysmal or persistent AF. The association between VER and LR was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
1
20
1
1
Order By: Relevance
“…However, histopathological studies have shown homogeneous lesion formation as early as 1 week after the CA, 18,19 and recently Xue et al have demonstrated that very ER, occurring within 7 days postablation, have a significant effect on LR. A sensitivity model showed that very ER had a greater prognostic value in predicting LR than common risk factors such as left atrial enlargement, age ≥65 years, and male gender 20 . Another recent study investigating the association between ER and LR using implantable loop recorders showed that not only the occurrence of ER, but also the AF burden significantly affects LR 21 …”
Section: Discussionmentioning
confidence: 99%
“…However, histopathological studies have shown homogeneous lesion formation as early as 1 week after the CA, 18,19 and recently Xue et al have demonstrated that very ER, occurring within 7 days postablation, have a significant effect on LR. A sensitivity model showed that very ER had a greater prognostic value in predicting LR than common risk factors such as left atrial enlargement, age ≥65 years, and male gender 20 . Another recent study investigating the association between ER and LR using implantable loop recorders showed that not only the occurrence of ER, but also the AF burden significantly affects LR 21 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study including paroxysmal and persistent AF had found that more than half of patients experienced VER after ablation during 7 days Holter recording (Arya et al., 2010) and a recent prospective study (Xue et al., 2017) shown that nearly one third of patient developed VER after AF ablation. Our study is consisted with these results which demonstrated that VER is common.…”
Section: Discussionmentioning
confidence: 99%
“…Technical parameters including dynamic range (±5 mV), input impedance (>10 MΩ), common mode rejection (≥60 dB), gain accuracy (≤10%), gain stability (≤3% over a 24‐hr period), system noise (<50uVp‐v), and frequency response (0.67–55 Hz) were set as factory setting. Patients were planned to be monitored for 7 days (Arya et al., 2010; Xue et al., 2017) and returned the device to research assistant after 7 days monitoring. Patients received both verbal and written instructions on how to use the device.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations